GM2 gangliosidosis future treatments 1 - Mark, Brian (Henry Stewart Talks, 2017)
Ganglioside catabolism and associated lysosomal storage diseases, Lysosomal hexosaminidase and turnover of GM2 ganglioside, Hexosaminidase mutations that cause GM2 gangliosidosis, Clinical progression of the disease, Experimental treatments